New anthropometric indices or old ones: Which is the better predictor of body fat?. Issue 4 (October 2017) - Ehrampoush, Elham; Arasteh, Peyman; Homayounfar, Reza; Cheraghpour, Makan; Alipour, Meysam; Naghizadeh, Mohammad Mehdi; hadibarhaghtalab, Maryam; Davoodi, Sayed Hosein; Askari, Alireza; Razaz, Jalaledin Mirzay
Abstract: Background: The percent and distribution of body fat are important factors in the pathogenesis of numerous diseases. Our aim was to investigate common anthropometric indices in their relationship with body fat content. Methods: In a cross-sectional study 1360 healthy individuals (580 men and 780 women) in a cluster sampling, from Ahvaz, Iran, body fat content (using bioelectrical impedance) and anthropometric measurements [weight, waist circumference, a body shape index, abdominal volume index, body adiposity index, conicity, body mass index, hip circumference, waist to hip ratio and waist to height ratio] was obtained. The ROC curve analysis was used to compare each index with body fat percent. Results: Significant difference was found between men and women in all anthropometric parameters (p < 0.001). Women displayed higher percentages in the overweight and obese categories (33.6% vs. 32.9% and 26.4% vs. 22.1%, respectively). In both men and women, the strongest correlations were seen between body fat percent and BMI, AVI and WHtR (r > 7.9 and p < 0.001). BMI, WHtR and AVI in men and BAI, BMI and WHtR in women showed the most accuracy for estimating body fat percent, respectively. Conclusion: All anthropometric parameters could predict body fat percent with relatively good power, however BMI, WHtR and AVI are more powerful predictors. Based on our findings, we suggest using the AVI and WHtR instead of other indexes, as they are better able to assess the accumulation of fat in the abdominal area and are able to more accurately assess body fat percent, which are indicators of chronic disease.